B2C e-commerce: the Italian market. (2nd November 2004) - Bertele, Umberto; Balocco, Raffaello; Gandini, Isabella; Rangone, Andrea
This article deals with the Italian B2C e-commerce market and serves two purposes. Firstly, the evolution of the business is described by reference to the principal results of a study carried out by an observatory of B2C electronic commerce in Italy promoted by the Associazione Impresa Politecnico, Idc Italia and The Boston Consulting Group [1]. Secondly, the main business models currently found in Italy are analysed with the help of some important cases.